Bioprocess enhancement of feather degradation using alkaliphilic microbial mixture. Issue 3 (4th May 2017) - Osman, Y.; Elsayed, A.; Mowafy, A. M.; Abdelrazak, A.; Fawzy, M.
ABSTRACT: 1. The main aim of this work is to develop a robust method to generate a microbial mixture which can successfully degrade poultry feathers to overcome environmental problems. 2. Four different alkaliphilic microbes were isolated and shown to degrade poultry feathers. 3. Two of the isolates were phylogenetically identified as Lysinibacillus and the others were identified as Nocardiopsis and Micrococcus. 4. The best microbial co-culture for white and black feather degradation was optimised for pH, temperature and relative population of the isolates to achieve almost 96% of degradation compared with a maximum of 31% when applying each isolate individually. 5. The maximum activity of keratinase was estimated to be 1.5 U/ml after 3 d for white feathers and 0.6 U/ml after 4 d for black feathers in a basal medium containing feather as the main carbon source. Additionally, non-denaturing polyacrylamide gel electrophoresis showed 4 and 3 protease activity bands for white and black feather, respectively. 6. This study provides a robust method to develop potential new mixtures of microorganisms that are able to degrade both white and black feathers by applying a Central Composite Design.